Applying quality function deployment for designing a cryogenic piping system. (16th March 2021) - Khan, Abid Hossain; Ahmed, S.M. Tazim; Rahman, Md. Sumon; Islam, Md. Shafiqul
Cryogenic piping system is a delicate product. If it is not designed properly, i.e., without considering region specific weather condition, vapourisation will occur at undesirable rate while cryogenic fluid flows through the pipeline. In this work, optimum design for a cryogenic piping system has been explored. To identify existing design limitations as well as customer priorities, quality function deployment has been employed. Data have been collected from local customers and experts through questionnaire-based survey. Double-concentric-pipes type construction with inner pipe diameter of 21.34-33.40 mm and outer pipe diameter of 88.90-193.68 mm has been considered. Four potential insulating mediums; multilayer insulation, vacuum, polyethylene foam, and perlite have been investigated. Multilayer insulation thickness and vacuum pressure have been varied from 6-30 mm and 10 −5 −5 mbar respectively. Results reveal that use of multilayer insulation accompanied by vacuum pressure of 10 −4 mbar ensures optimum performance with optimum insulation thickness of 20 mm.